Znaczenie sektora non profit - Doniec, Alicja (Significance of the Non-Profit Sector, 2006)
The unhomogenic nature of the third sector in the current social and commerce life in the democratic states is the main subject of the work. Characteristics of the non profit sector is made according to its basic functions and features, that diverse the sector from the public sector, as well as form the private for - profit area. Defining the sector is also tied with the question of professional management implementation in the non profit organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 243-252